A Survey on Efficient Heart Disease Prediction Technique - et. al., Thilagamani S , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper is a survey on different heart disease prediction technique to predict and diagnosis of heart diseases. In order to increase the efficiency and accuracy of the prediction process an effective method is to be searched. For this searching process , data mining and machine learning techniques are recommended. The main purpose of this paper is to improve cardiac problem diagnostic method, by including early diagnosis warning method.